Evaluating spatial efficiency and equity in urban structure: An accessibility study - Kelobonye, Keone (Curtin University, 2020)
Cities are living organisms; they are born, they grow and eventually die. The spatial arrangement of land uses within a city and the quality of transport networks connecting them can be the difference between a struggling city and a thriving one. This thesis develops a robust and comprehensive framework for evaluating the spatial efficiency and spatial equity of urban structure. Measures for optimising the efficiency of travel and equitable service access within cities are proposed.